Early childbearing : perspectives of Black adolescents on pregnancy, abortion, and contraception - Freeman, Ellen W. (Sage library of social research ;, 1993)
The challenge of reaching teenagers before an unintended pregnancy occurs is particularly pertinent when considering unmarried teenagers from disadvantaged circumstances: while the incidence of teenage pregnancy increases, resources to assist adolescents in both child care and employment are lacking. This volume presents a thorough and sensitive exploration of the topic of sexually active teenagers and the factors involved in their decisions about contraception, abortion and childbearing. The authors conducted their research among African Americans, aged from 13 to 17, living in deprived, urban areas. They describe the teenagers' attitudes about childbearing relative to other goals and perceived attitudes of family and friends; they conclude that pregnancy is seen as a choice based on perceptions of childbearing in the psychosocial context of their lives